Burden and Transmission Risks of Viral Hepatitis in Southern Ethiopia: Evidence Needed for Prevention and Control Measures - Beykaso G (Dove Medical Press, 2021)
Gizachew Beykaso,1,2 Andargachew Mulu,3 Mirutse Giday,1 Nega Berhe,1 Markos Selamu,2 Adane Mihret,3 Tilahun Teklehaymanot1 1Department of Molecular Biology and Immunology, Aklilu Lemma Institute of Pathobiology, Addis Ababa University, Addis Ababa, Ethiopia; 2Department of Public Health, College of Medicine and Health Sciences, Wachemo University, Hossana, Ethiopia; 3Department of Virology, Armauer Hansen Research Institute, Addis Ababa, EthiopiaCorrespondence: Gizachew BeykasoDepartment of Public Health, College of Medicine and Health Sciences, Wachemo University, PO Box 667, Hossana, EthiopiaTel +251-91-206-6531Email gbeykaso88@gmail.comBackground: Hepatitis B virus (HBV) and hepatitis C virus (HCV) are significant causes of liver-associated morbidity and mortality for millions of people globally. Ethiopia is one of the viral hepatitis–endemic countries with no national strategy for surveillance and limited data. As such, this study aimed to investigated the extent and associated risk factors of HBV and HCV among community members in southern Ethiopia.Methods: A community-based cross-sectional study was conducted from January 2020 to August 2020. A structured questionnaire was used to collect behavioral and sociodemographic data. Serum samples were collected and assayed for seromarkers of HBV (HBsAg, anti-HBc, and anti-HBs) and HCV (anti-HCV) using ELISAs. In HBsAg-positive samples, HBV DNA was further quantified using RT-PCR. Data were entered into EpiData 3.1 and analyzed using SPSS 21.0. Descriptive statistics and logistic regression analysis were employed.Results: The study included 693 participants. Seromarkers for HBsAg, anti-HCV, anti-HBc, and anti-HBs were found to be 9.5%, 1.4%, 31.1%, and 14.3%, respectively. In 66 HBsAg positives, 57 (86.4%) had quantifiable HBV DNA. Prevalence of current HBV infection (HBsAg+, anti-HBc+, anti-HBs–) and lifetime exposure (positive for either HBsAg or anti-HBc) to HBV were 8.7% and 31.9%, respectively, and 63.1% of participants were vulnerable or had no evidence of prior HBV infection (HBsAg–, anti-HBc–, anti-HBs–). On multivariate logistic regression analysis, multiple sexual contacts, family history of hepatitis infection, alcohol consumption, and khat chewing were significantly associated with HBV. The seroprevalence of HBV was relatively high in this study area.Conclusion: This study showed high prevalence of HBV infection, but low prevalence of HCV. This indicates that HBV is a major health problem in this community. Population-based surveillance, care, and treatment, as well as behavioral change and education programs, should be enhanced to minimize risk exposure.Keywords: community-based, HBV, HCV, seroprevalence, southern Ethiopia